Pengaruh Konsentrasi dan Frekuensi Aplikasi Pupuk Daun Cair Terhadap Pertumbuhan Bibit Aquilaria malaccencis Lamk. - Sri Wulandari; Nelly Anna; Edy Batara Mulya Siregar (Program studi Kehutanan USU, 2015)
Fertilizationis a means or method used for fertilizer through the leaves and plant part slain.The purpose of this study was to determine the frequency of fertilization and foliar fertilizer concentration is best for seedling growth aloes (A. malaccensisLamk.). The samples used were aloe plant seeds that have been aged 3 months were taken from CV. Earth Partners II, Land of a Thousand Village, city Binjai, North Sumatra. Nursery heldon the 4th floor of buildings Forestry Faculty of Agriculture, University of North Sumatra, which was conducted in November-January2013. The results showed that the frequency of the treatment of liquid foliar fertilizer application significantly affected the height and number of leaves.Treatment of liquid foliar fertilizer concentration significantly affected the number of leaves.The interaction frequency and concentration of liquid foliar fertilizer application significantly affected height and number of leaves. Keywords: fertilization, agarwood, frequency, concentration